2007
DOI: 10.1186/1465-9921-8-25
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of decline in fat free mass and skeletal muscle strength in chronic obstructive pulmonary disease

Abstract: Decline in fat free mass in COPD is associated with worse lung function, continued cigarette consumption and frequent exacerbations. Factors predicting progression of quadriceps weakness could not be identified from the present cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
114
1
13

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(139 citation statements)
references
References 50 publications
11
114
1
13
Order By: Relevance
“…Moreover, small but signifi cant reductions in quadriceps muscle strength 10 and peak V O 2 11,12 were found in (mostly male) COPD patients over a 1 to 5 year period, respectively. To the best of our knowledge, this is the fi rst study to show an agegraded reduction in quadriceps muscle strength and peak V O 2 in patients with COPD after correction for possible confounding factors, such as gender, LL-LMM, and D L CO. More importantly this study corroborates the previously identifi ed decrease in lower-limb muscle function in patients with COPD 3,16 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, small but signifi cant reductions in quadriceps muscle strength 10 and peak V O 2 11,12 were found in (mostly male) COPD patients over a 1 to 5 year period, respectively. To the best of our knowledge, this is the fi rst study to show an agegraded reduction in quadriceps muscle strength and peak V O 2 in patients with COPD after correction for possible confounding factors, such as gender, LL-LMM, and D L CO. More importantly this study corroborates the previously identifi ed decrease in lower-limb muscle function in patients with COPD 3,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Hopkinson at al. 10 reported a non-significant decline of 0.2 kilogram in fat-free mass during a 1-year follow-up period in 64 COPD patients 10 . Also in the current cross-sectional analyses no age-graded reductions in LL-LMM were found, except for the older male COPD patients with a D L CO >50% predicted (Figure 3d and Table E6 of the online supplement).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, lower limb muscle weakness is more prevalent than loss of whole body fat free mass (24,25) in COPD. Secondly, it has been clearly demonstrated that rectus femoris cross sectional area and quadriceps maximal voluntary contraction force are reduced in patients with mild disease, in whom there is only minimal pulmonary impairment to exercise (26).…”
Section: Accepted Manuscriptmentioning
confidence: 99%